Ehrlichia minasensis sp. nov., isolated from the tick Rhipicephalus microplus - Cabezas-Cruz, Alejandro; Zweygarth, Erich; Vancová, Marie; Broniszewska, Marzena; Grubhoffer, Libor; Passos, Lygia Maria Friche; Ribeiro, Múcio Flávio Barbosa; Alberdi, Pilar; de la Fuente, José (International journal of systematic and evolutionary microbiology, 2016)
Recently, we obtained a rickettsial isolate (Ehrlichia sp. UFMG-EVT) from the haemolymph of engorged Rhipicephalus microplus tick females. On the basis of maximum-likelihood phylogenetic analysis using 16S rRNA gene, groEL, dsb, gltA and trp36 sequences we showed that Ehrlichia sp. UFMG-EVT belongs to the α-Proteobacteria, family Anaplasmataceae, genus Ehrlichia. Ehrlichia sp. UFMG-EVT is a sister taxon of Ehrlichia canis with 16S rRNA gene, groEL, dsb, gltA and trp36 sequence similarities of 98.3 %, 97.2 %, 94.7 %, 94.3 % and 49.1 %, respectively. Ehrlichia sp. UFMG-EVT has been maintained in the laboratory by continuous passage in the IDE8 tick cell line where the ultrastructure was characterized using electron microscopy and was found to resemble that of E. canis, Ehrlichia muris and Ehrlichia chaffeensis, but not Ehrlichia ruminantium and Ehrlichia ewingii. We propose the name Ehrlichia minasensis sp. nov. for this bacterium to acknowledge the place from where it was initially isolated, Minas Gerais, Brazil. The type strain is strain Ehrlichia sp. UFMG-EVT ( = DSM 100393T = TCB-TBB-0018T).